Variation in the Soil Prokaryotic Community Under Simulated Warming and Rainfall Reduction in Different Water Table Peatlands of the Zoige Plateau - Li, Wei; Chen, Huai; Yan, Zhiying; Yang, Gang; Rui, Junpeng; Wu, Ning; He, Yixin (Frontiers in Microbiology, 2020)
Climate change and water table drawdown impacts the community structure and diversity of peatland soil prokaryotes. Nonetheless, how soil prokaryotes of different water tables respond to climate change remains largely unknown. This study used 16S rRNA gene sequencing to evaluate the variation in soil prokaryotes under scenarios of warming, rainfall reduction, and their combination in different water table peatlands on the Zoige Plateau in China. Stimulated climate change affected some of the diversity indexes and relative abundances of soil prokaryotes in three water table peatlands. Additionally, those from the dry-rewetting event peatland had the most dominant phyla (genera) that showed significant changes in a relative abundance due to the simulated climate change treatments. Regarding functional microbial groups of carbon and nitrogen cycling, simulated climate change did not affect the abundances of the Euryarchaeota, Proteobacteria, Verrucomicrobia, and Methanobacterium in three water table peatlands, except NC10 and Nitrospirae. Redundancy analysis showed that the prokaryotic community variation was primary impacted by site properties of the different water table peatlands rather than the simulated climate change treatments. Moreover, the water table, total carbon, total nitrogen, and soil pH were the primary factors for the overall variation in the soil prokaryotic structure. This study provides a theoretical guidance for management strategies in the Zoige peatland, under climate change scenarios. More attention should be given to the interactive effects of peatland water table drawdown and simulated climate changes for better restorative efforts in water table drawdown, rather than simply adapting to climate change.